Tinggalan Tradisi Megalitik Di Desa Keramas, Kecamatan Blahbatuh, Kabupaten Gianyar - Wisnu Saputra, Kadek; Ardika, I Wayan; ., Zuraidah (Humanis; Volume 16. No. 1. Juli 2016, 2016)
Bali is one island in Indonesia that holds a lot of evidence remains megalitik.Salah tradition of the evidence of the megalithic tradition in Bali is found in the village of Keramas, Blahbatuh, Gianyar. The objects are mostly stored in the form of several temples except the remains of a sarcophagus that is now stored in the Institute for Preservation of Cultural Heritage (BPCB) Bali, NTB, NTT. Th e first re searct ini Keramas village was did by the survey team of the Archeological Research center and National Heritage Jakarta on 25 March 1976 led by Ismanto Kosasih, SA. The team initially examined the sarcophagus was found by villagers shampooing when making foundation Keramas village hall in 1975. research has the objective to determine the type, function and meaning of the remains of the megalithic tradition in the village of Keramas, Blahbatuh, Gianyar. The theory used in this research is the theory of structural functionalism and theory of semiotics. The method used in this study, the data collection phase is done by observation, interview and literature study, then the second stage of data processing by analyzing data using morphological analysis techniques, stylistic analysis and comparative analysis. From the analysis it can be concluded that the remains of the megalithic tradition in Keramas village is divided into several types, including simple statues, animal statues, statues patterned megalithic stone mortar, sarcophagus and menhirs. Function remains of the megalithic tradition in the village of Keramas as media homage to the ancestors is shown in statues simple Besakih, the statue of Lord-goddess in the temple Sekah, statues patterned megalithic in Pura Pasek Ngukuhin and sarcophagus found in the village of Keramas but the sarcophagus is profane or no longer functioned. Megalithic remains at Keramas village which has a function as a symbol of fertility, among others, stone mortars in Sedaan Purwa, Arca animals Bawi Siati and menhirs in Besakih is a symbol of fertility and media worship of the Goddess of Earth and Gods Wisnu.Tinggalan megalithic tradition in the village of Keramas has meaning fertility and religious significance.